Goal impact influences the evaluative component of performance monitoring: Evidence from ERPs - Severo, Mario Carlo; Walentowska, Wioleta; Moors, Agnes; Pourtois, Gilles (Biological psychology, 2017)
•Goal impact influences outcome evaluation during performance monitoring.•The amplitude of the FRN decreases as goal impact increases.•The amplitude of the P3 increases when goal impact increases.•These effects suggest that motivation influences performance monitoring. Successful performance monitoring (PM) requires continuous assessment of context and action outcomes. Electrophysiological studies have reliably identified event-related potential (ERP) markers for evaluative feedback processing during PM: the Feedback-Related Negativity (FRN) and P3 components. The functional significance of FRN remains debated in the literature, with recent research suggesting that feedback’s goal relevance can account for FRN (amplitude) modulation, apart from its valence or expectedness alone. Extending this account, the present study assessed whether graded differentiations in feedback’s relevance or importance to one’s goal (referred to as goal impact) would influence PM at the FRN (and P3) level. To this end, we ran a within-subject crossover design experiment in which 40 participants completed two standard cognitive control tasks (Go/No Go and Simon), while 64-channel electroencephalography was recorded. Critically, both tasks entailed similar reward processing but systematically varied in goal impact assignment (high vs. low), manipulated through their supposed diagnosticity for daily life functioning and activation of social comparison. ERP results showed that goal impact reliably modulated FRN in a general manner. Irrespective of feedback valence, it was overall less negative in the high compared to the low impact condition, suggesting a general decrease in feedback monitoring in the former compared to the latter condition. These findings lend support to the idea that PM is best conceived operating not solely based on motor cues, but is shaped by motivational demands.